Compensación y devolución del saldo a favor del exportador de la Empresa Cusco Trans E.I.R.L. Periodo 2016-2019 - Ramírez Alejos, Paola Angela (2023)
The study entitled “Compensation and return of the balance in favor of the exporter of the company Cusco Trans E.I.R.L. period 2016-2019”, being useful for the company's stakeholders, since investors will be able to evaluate its convenience and apply it, to improve the competitiveness of the company. The objective was to determine the value of the Balance in favor of the Benefit for compensation and return of the balance in favor of the exporter the company CUSCO TRANS E.I.R.L. For this purpose, the quantitative approach, descriptive scope and non-experimental – longitudinal design was used; The population and sample were the accounting and tax documents, the import and export declarations, records of purchases and sales of the company. For data collection, the documentary analysis technique was used, the instrument used was the documentary analysis sheet. Regarding the results obtained, it was evidenced that, in December 2015, an SMFB Object of Return of S / 160'226 was determined, for the year 2016 of S / 749'236, for the year 2017 of S / 1'593'594, for the year 2018 of S / 2'217'738, for the year 2019 of S / 2,749,914 and for the year 2020 an accumulated of S / 2'837'443. Finally, it was concluded that the company did not request the return of the balance in favor of the exporter during the study period, in addition the existence of balances in favor of the company CUSCO TRANS E.I.R.L.